An Investigation of School Violence and Pre-Service Teachers - Karen Nykorchuk McCaleb; Amy Andersen; Harry Hueston (Arizona State University, 2015)
All educators need to be aware of issues regarding school violence. Recent years have shown that violence can happen in a variety of school settings. This study conducted a one-group, pretest-posttest, pre-experimental design to explore pre-service teachers perceptions regarding school violence. First, pre-service educators were asked to complete an online, anonymous survey. Next, the participants, members of the same English/Language Arts Methods class, were taught a three-part school violence curriculum. And finally, a posttest, optional and anonymous, was administered. Results suggest that there was a change in respondents perceptions regarding school violence after having participated in the curriculum.